ASH1L histone methyltransferase regulates the handoff between damage recognition factors in global-genome nucleotide excision repair - Balbo Pogliano, Chiara; Gatti, Marco; Rüthemann, Peter; Garajovà, Zuzana; Penengo, Lorenza; Naegeli, Hanspeter (Nature communications, 2017)
Global-genome nucleotide excision repair (GG-NER) prevents ultraviolet (UV) light-induced skin cancer by removing mutagenic cyclobutane pyrimidine dimers (CPDs). These lesions are formed abundantly on DNA wrapped around histone octamers in nucleosomes, but a specialized damage sensor known as DDB2 ensures that they are accessed by the XPC initiator of GG-NER activity. We report that DDB2 promotes CPD excision by recruiting the histone methyltransferase ASH1L, which methylates lysine 4 of histone H3. In turn, methylated H3 facilitates the docking of the XPC complex to nucleosomal histone octamers. Consequently, DDB2, ASH1L and XPC proteins co-localize transiently on histone H3-methylated nucleosomes of UV-exposed cells. In the absence of ASH1L, the chromatin binding of XPC is impaired and its ability to recruit downstream GG-NER effectors diminished. Also, ASH1L depletion suppresses CPD excision and confers UV hypersensitivity. These findings show that ASH1L configures chromatin for the effective handoff between damage recognition factors during GG-NER activity. UV-induced mutagenic cyclobutane pyrimidine dimers on nucleosomal DNA are sensed by the damage recognition factors DDB2 and XPC via an unknown mechanism. Here, the authors show that the histone methyltransferase ASH1L regulates the DDB2 to XPC handoff by methylating Lys-4 of histone H3.